Preparation method and application of magnetic nanorod
β-FeOOH nanorods were synthesized and modified by polyol reduction method to form R-Fe3O4@PSSMA with magnetic responsiveness and peroxidase activity, which solved the shortcomings of existing magnetic nanoparticles in terms of catalytic activity and stability, and achieved the goal of achieving Efficient quantitative detection and catalytic reaction in microfluidic control systems.
Patent Information
- Application Number
- CN202411436439.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
Existing magnetic nanoparticles have shortcomings in catalytic activity, stability and specific identification, especially in small scales and complex environments, and traditional stirring methods are not suitable for microfluidic systems.
Polyol reduction method was used to synthesize β-FeOOH nanorods with anisotropy in aqueous solution, and R-Fe3O4@PSSMA was modified to form R-Fe3O4@PSSMA, using its magnetic responsiveness and peroxidase activity as dynamic nanoenzymes. Quantitative detection and catalytic reactions in microfluidic control systems.
The preparation of magnetic nanorods with controllable morphology has been realized, which significantly improves catalytic activity and dispersion, enhances the specific recognition ability of target compounds, and effectively reacts and mixes on a small scale, which is suitable for microfluidic systems. Quantitative detection.
Smart Images

Figure CN119281303A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a magnetic nanorod, and in particular to a preparation method and application of the magnetic nanorod Background Art
[0002] In 2007, the team of Academician Yan Xiyun discovered that ferromagnetic nanoparticles have inherent peroxidase activity, similar to natural horseradish peroxidase. Although Fe3O4 nanoparticles have the advantages of good stability, low cost, and simple production as mimics of natural peroxidase, there is still some room for improvement. One of the main challenges is to increase the catalytic activity while improving the stability and dispersibility of the nanoparticles and enhancing the specific recognition of the target compounds. To overcome these challenges, it is necessary to design new modification methods and develop synergistic materials to regulate the activity of Fe3O4 nanoparticles and maintain their properties.
[0003] For magnetic nanomaterials, morphology and shape anisotropy have an important influence on their performance. Taking magnetic nanorods as an example, when the direction of the easy magnetization axis of magnetic nanoparticles coincides with the direction of shape anisotropy, the magnetic properties of magnetic nanoparticles are better. In addition, compared with spherical nanoparticles, rod-shaped nanoparticles (nanorods) or worm-shaped nanoparticles have a larger contact area with the cell membrane, and their slender shape enables them to cross the cell barrier more effectively and be more easily absorbed by the cell membrane through the endocytic mechanism. In addition, the specific absorption rate (SAR) of magnetic nanorods has also been shown to be stronger than that of spherical magnetic nanoparticles. Secondly, magnetic nanorods show higher specificity in drug delivery than spherical nanoparticles. Finally, the magnetic anisotropy of magnetic nanorods also provides potential possibilities for catalysis, small-scale stirring and other applications.
[0004] Therefore, in the preparation of magnetic nanomaterials, people pay more attention to the preparation process and the particle size distribution of nanoparticles, but less attention is paid to the control of particle morphology. In addition, in order to promote mass transfer, the rapid and effective mixing of reactants and catalysts is crucial in liquid reaction systems. However, due to the macroscopic size of the magnetic rod, the conventional magnetic stirring method is impractical for ultra-small systems such as chip laboratories and flow cells.
[0005] Therefore, it is urgent to develop a mild and controllable method to synthesize shape-anisotropic magnetic nanorods with catalytic properties. Summary of the invention
[0006] Purpose of the invention: The present invention develops a simple strategy to synthesize magnetic nanorods with peroxidase (POD) activity, which can be used as nanozymes and magnetic stirring nanorods for microcatalytic reactions. The magnetic nanorods are used in microfluidic systems to achieve quantitative detection of analytes.
[0007] Technical Solution
[0008] A method for preparing magnetic nanorods, characterized in that the method is implemented according to the following steps:
[0009] (1) Preparation of β-FeOOH nanorods
[0010] FeOOH nanorods were synthesized by hydrolyzing FeCl3·6H2O in aqueous solution; the concentration of FeCl3·6H2O was 0.01-0.04 mol L at a constant temperature of 25°C. -1 After 10-100 days of reaction, the FeOOH nanorods formed are precipitated to the bottom of the reaction vessel to form a β-FeOOH nanorod solution;
[0011] (2) Preparation of R-Fe3O4@PSSMA
[0012] 3 mL of β-FeOOH nanorod solution was centrifuged at 8500 rpm for 5 minutes, vacuum dried, 20-80 mL of ethylene glycol was added, and then 0.3-10 g of anhydrous sodium acetate, 0.5-2.0 g of PSSMA, 5-50 mg of ascorbic acid and water were added, and stirred to dissolve; the solution was reacted in a muffle furnace at 150-250°C for 6-12 hours to obtain magnetic nanorods R-Fe3O4@PSSMA;
[0013] (3) Preparation of R-Fe3O4@PVP
[0014] 3 mL of β-FeOOH nanorod solution was centrifuged at 8500 rpm for 5 minutes, vacuum dried, and the powder was taken to continue the reaction, and 30 mL of ethylene glycol was added. 0.3-10 g of sodium acetate, 0.5-2.0 g of polyvinyl pyrrolidone, and 0.11 g of glucose were added in sequence, and then the mixed solution was ultrasonically dispersed, and the resulting solution was transferred to a polytetrafluoroethylene liner and reacted at 220 ° C for 12 hours to obtain R-Fe3O4@PVP.
[0015] The method described is used to prepare magnetic nanorods for use as peroxidase.
[0016] As an optimization:
[0017] The preparation method of magnetic nanorods is achieved by the following steps:
[0018] (1) Preparation of β-FeOOH nanorods
[0019] Nanorods with different aspect ratios can be synthesized by hydrolyzing FeCl3·6H2O in aqueous solution. β-FeOOH nanorods with uniform morphology and size were synthesized at a constant temperature of 25°C. The size and morphology of FeOOH nanorods can be further controlled by controlling the reaction time and reaction temperature. The total volume during hydrolysis was 4 L. The concentration of FeCl3·6H2O was 0.04 mol L -1 After a period of reaction, the formed β-FeOOH nanorods were precipitated to the bottom of the reaction vessel (one month). After removing the supernatant, the FeOOH nanorods were washed three times by centrifugation at 10,000 rpm and then dispersed in 40 mL of water as a stock solution.
[0020] (2) Preparation of R-Fe3O4@PSSMA
[0021] 3mL of β-FeOOH mother liquor was centrifuged at 8500rpm for 5 minutes, vacuum dried, and the powder was taken to continue the reaction, and 40mL of ethylene glycol was added. Note that the ethylene glycol must be dehydrated with 3A molecular sieves overnight in advance. Then add 3.0g of anhydrous sodium acetate, 1.1g of PSSMA, a small amount of ascorbic acid (Vc) and an appropriate amount of water, seal the beaker with paraffin film or plastic wrap, and then stir and dissolve with ultrasonic + magnetic force alternately; after dissolution, transfer the solution to 50mL polytetrafluoroethylene lining and react in a muffle furnace at 190°C for 9 hours. After the reaction is completed, cool to room temperature and wash three times with ultrapure water;
[0022] (3) Preparation of R-Fe3O4@PVP
[0023] 3 mL of β-FeOOH mother liquor was centrifuged at 8500 rpm for 5 minutes, vacuum dried, and the powder was taken to continue the reaction, and 30 mL of ethylene glycol was added. 0.99 g of sodium acetate, 0.99 g of polyvinyl pyrrolidone, and 0.11 g of glucose were added in sequence, and then the mixed solution was ultrasonically dispersed, and the resulting solution was transferred to a polytetrafluoroethylene liner and reacted at 220 ° C for 12 hours. After the reaction was completed, it was cooled to room temperature and washed three times with ultrapure water.
[0024] The magnetic nanorods are used as peroxidase.
[0025] Research ideas of the present invention:
[0026] (1) The rod-shaped non-magnetic iron oxyhydroxide was reduced to magnetic nanorods by the polyol reduction method. First, FeCl3·6H2O was hydrolyzed in an aqueous solution, and nanorods with different aspect ratios were synthesized by adjusting the reaction temperature, reaction time, and adding different compounds. Then, FeOOH was reduced to magnetic nanorods. We tried a variety of polymers as protective ligands, such as polyvinylpyrrolidone (PVP) and poly(4-styrenesulfonic acid-comaleic acid) sodium (PSSMA). It is hoped that under the protection of the polymer ligand, the morphology of the anisotropic particles can be protected during the phase transition process, thereby enabling the controllable preparation of magnetic nanorods.
[0027] (2) The prepared magnetic nanorods can self-assemble into magnetically responsive, micrometer-sized magnetic chains through modified polymer ligands (PSSMA). In addition to magnetic field responsiveness, the magnetic chains also have peroxidase-like activity, which we use as dynamic nanozymes. We further explore the optimal reaction conditions of the dynamic nanozyme at different pH and temperature to obtain the steady-state kinetic parameters of the dynamic nanozyme, the maximum initial reaction rate (V max ) and the Michaelis-Menten constant (K m ). A dynamic nanozyme system was constructed based on magnetic nanorods to quantitatively detect cysteine.
[0028] Innovation
[0029] (1) Innovation of synthetic methods:
[0030] At present, many methods for synthesizing spherical Fe3O4 nanoparticles have been reported, while there are few reports on non-spherical Fe3O4 nanoparticles because it is difficult to grow an asymmetric structure from a material with a highly symmetrical cubic crystal structure. The present invention adopts a mild method to prepare intelligent magnetic nanorods with controllable morphology and size. We use a polyol reduction method to reduce rod-shaped non-magnetic iron hydroxide to magnetic nanorods. FeCl3·6H2O is hydrolyzed in an aqueous solution, and nanorods with different aspect ratios can be synthesized by regulating parameters such as reaction temperature and reaction time. The method has mild conditions, is green, and has stronger controllability for particle size. Then, FeOOH is reduced to magnetic nanorods. We use PSSMA poly(4-styrenesulfonic acid-co-maleic acid) sodium as a protective ligand. PSSMA poly(4-styrenesulfonic acid-co-maleic acid) sodium has rich anionic groups (-COO- and -SO3-). PSSMA is modified on magnetic nanoparticles, and the morphology of anisotropic particles can be protected during the phase transition process. At the same time, by using polymers as shape-protecting capping agents, the synthesis temperature is greatly reduced compared to hydrogen reduction. It also solves the problem of poor dispersion of traditional dense protective layers during high-temperature phase transitions and greatly improves the synthesis efficiency.
[0031] (2) Application innovation:
[0032] We propose to use self-assembled magnetic chains as dynamic nanozymes, and use the magnetic responsiveness of the magnetic chains to increase the mixing of the reaction system and further improve the reaction kinetics. In addition to magnetic field responsiveness, the magnetic chain also has peroxidase-like activity, which we use as a dynamic nanozyme. And a dynamic nanozyme system based on the magnetic chain is constructed to quantitatively detect cysteine. For a typical conventional stirring system, due to the adsorption of reactants on the stirring device, the stirring process may cause a certain degree of loss of reactant species and catalysts (used to catalyze the reaction), thereby affecting the generated products. In addition, recent studies have shown that the surface of the magnetic stirring bar is susceptible to microscopic damage, resulting in the defect of capturing trace metals (such as gold, palladium, platinum, iron, etc.) from the reaction mixture. Traditional cleaning processes are not necessarily sufficient to eliminate these trapped metal species, so these trapped metal impurities inadvertently have a significant impact on the chemical reaction rate. In addition, traditional stirrers are limited by their size, while magnetic nanorods can act as nanoscale magnetic stirrers in tiny reaction systems due to their magnetic anisotropy. This nanoscale stirrer will promote the reaction on a smaller scale and is expected to be used in tiny volume reactions.
[0033] Beneficial Effects
[0034] In the preparation research of magnetic nanomaterials, people pay more attention to the preparation process and the particle size distribution of nanoparticles, but less attention is paid to the control of particle morphology. For magnetic materials, particle morphology and shape anisotropy have an important influence on the magnetic properties of particles, especially when the easy magnetization axis of the particle coincides with the direction of particle shape anisotropy, the magnetic properties of the particle are better. However, there are relatively few literatures on nanorods, mainly because it is challenging to grow a one-dimensional structure from a material with a highly symmetrical cubic crystal structure, and from an energy perspective, it is more inclined to generate isotropic spherical nanoparticles. At present, the two most commonly used methods for synthesizing magnetic nanorods with shape anisotropy are to form magnetic nanorods directly from pentacarbonyl iron precursors, and to first generate nanorods in the FeOOH crystal form and then reduce the compound to form an iron oxide phase. The one-step synthesis of magnetic iron oxide nanorods reported in the literature either uses customized reagents or has very poor magnetic properties. The difficulty in forming elongated iron oxide structures is directly related to the fact that its cubic crystal structure has no preferred orientation for growth. To this end, different surfactants are used to prevent the growth of some crystal planes and allow the growth of other crystal planes, resulting in anisotropic iron oxide nanoparticles. In contrast, even in the absence of any surfactant, many polymorphs of FeOOH often crystallize in the form of elongated structures. Magnetic nanorods were easily synthesized in two steps, first by producing FeOOH through a simple hydrolysis, which is then converted into iron oxide through a reduction procedure. However, the two-step synthesis method also has its limitations, and some results show that the morphology of the nanorods changes after reduction due to changes in the crystal structure.
[0035] In addition, the chemical conversion method has some limitations, including severe reaction conditions and the fact that chemical reactions can cause the initial morphology of anisotropic nanoparticles to change or even agglomerate with each other. By using a layer of inorganic material as a template, such as a coating of silica, changes in morphology and structure during the chemical conversion process can be effectively avoided. The silica shell plays a role of spatial confinement during the chemical conversion process, which is why the morphology of the anisotropic particles can be protected. However, because the silica layer is too dense, it often prevents the transfer of substances between the particles in the confined space and the external environment, which requires more stringent reaction conditions in the chemical conversion process, resulting in increased costs and energy waste, such as increasing the reaction temperature. Although increasing the reverse temperature can complete the phase transition, it will cause serious particle agglomeration, making the dispersion of the magnetic particles worse.
[0036] Therefore, it is urgent to develop a controllable and mild method to prepare magnetic nanorods.
[0037] The present invention adopts a polyol reduction method to reduce rod-shaped non-magnetic iron oxyhydroxide into magnetic nanorods. Nanorods with different aspect ratios can be synthesized by hydrolyzing FeCl3 in an aqueous solution. FeOOH nanorods with uniform morphology and size are synthesized at a constant temperature of 25°C by regulating the reaction temperature. Therefore, the size and morphology of the magnetic nanorods can be further regulated by controlling the reaction time and reaction temperature. We use poly(4-styrenesulfonic acid-comaleic acid) sodium (PSSMA) as a protective ligand. PSSMA has abundant anionic groups (-COO- and -SO 3- ), PSSMA is modified on magnetic nanoparticles, and the morphology of anisotropic particles can be protected during the phase transition process. At the same time, the use of polymers as end-capping agents for shape protection greatly reduces the synthesis temperature compared to hydrogen reduction. At the same time, it also solves the problem of poor dispersibility of traditional dense protective layers during high-temperature phase transitions, and greatly improves the synthesis efficiency.
[0038] Magnetic nanorods are used as dynamic nanozymes. The magnetic nanorods, through modified polymer ligands (PSSMA), can self-assemble into magnetically responsive, micron-sized magnetic chains. In addition to magnetic field responsiveness, the magnetic chain also has peroxidase-like activity, and we use it as a dynamic nanozyme. We further explored the optimal reaction conditions of the dynamic nanozyme at different pH and temperature to obtain the steady-state kinetic parameters, maximum initial reaction rate (Vmax) and Michaelis-Menten constant (Km) of the dynamic nanozyme. And a dynamic nanozyme system is constructed based on magnetic nanorods to quantitatively detect cysteine. Compared with static nanozymes, the enzyme activity of dynamic nanozymes can be up to 3 times the original, which significantly enhances the reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 β-FeOOH prepared from (a) FeCl3 and (b) FeCl3·6H2O;
[0040] Figure 2 Effect of different reaction temperatures on the preparation of β-FeOOH;
[0041] Figure 3 The effect of adding different compounds on the formation of β-FeOOH;
[0042] Figure 4 Effect of different reaction times on the growth of β-FeOOH;
[0043] Figure 5 The lengths of the major and minor axes of β-FeOOH at different reaction times;
[0044] Figure 6(a) XRD spectrum of β-FeOOH, (b) IR spectrum of β-FeOOH;
[0045] Figure 7 (a) and (c) are the XPS spectra of magnetic nanorods, (b) the XRD spectrum of magnetic nanorods, (d) the infrared spectrum of magnetic nanorods, and (e) the BET spectrum of magnetic nanorods;
[0046] Figure 8 Transmission electron microscopy images of the morphology of magnetic nanorods protected by different ligands; a is ATPES, b is SiO2, c is PSSMA, and d is PVP;
[0047] Fig. 9 Electron microscopy images of the morphology of magnetic nanorods protected by different ligands: (a) and (c) are R-Fe3O4@PVP; (b) and (d) are R-Fe3O4@PSSMA; (e) and (f) are length-width distribution diagrams;
[0048] Fig.10 (a) Magnetic hysteresis loops of R-Fe3O4@PVP and R-Fe3O4@PSSMA (solid powder). (b) Extended low-field curves (solid powder). (c) Magnetic hysteresis loops of R-Fe3O4@PVP and R-Fe3O4@PSSMA (liquid, concentration of 10 mg / ml). (d) Extended low-field curves (liquid, concentration of 10 mg / ml);
[0049] Fig.11 Comparison of magnetic properties between magnetic fluids prepared from magnetic nanorods and magnetic fluids prepared from spherical magnetic nanoparticles;
[0050] Fig.12 COMSOL Multiphysics simulation results of magnetic nanorods;
[0051] Fig.13 (a) Schematic diagram of the preparation of magnetic nanorods, (b) Schematic diagram of the principle of cysteine detection;
[0052] Fig.14 Dark-field optical microscopy images of PSSMA-coated magnetic nanorods after self-assembly, (a) without magnetic field; the red arrows in (b), (c) and (d) represent the direction of the magnetic field;
[0053] Fig.15(a)(b) Dark field optical microscopy images of self-assembly of spherical magnetic nanoparticles coated with PSSMA (c) Dark field optical microscopy images of magnetic nanoparticles coated with PVP, (d) Dark field optical microscopy images of magnetic nanorods coated with PVP (e) Schematic diagram of dark field optical microscopy of solid powder of R-Fe3O4@PSSMA (f) Zeta potential of R-Fe3O4@PSSMA under different pH conditions;
[0054] Fig.16 Relative activity of TMB oxidation reaction at different rotation speeds;
[0055] Fig.17 (a) Absorption spectrum of the reaction of substrates OPD and ABTS catalyzed by R-Fe304@PSSMA (b) The black curve is the UV absorption spectrum after incubation with TMB+H2O2, the red curve is the UV absorption spectrum after incubation with TMB+H2O2+R-Fe304@PSSMA, and the blue curve represents the UV absorption spectrum after incubation with TMB+H2O2+R-Fe304@PSSMA under a rotating magnetic field. (c) ESR graph of free radicals generated by magnetic nanorods (d) Control experiment of oxidation of TMB by free radical scavenger DMSO. DETAILED DESCRIPTION
[0056] Example 1 Preparation of magnetic nanorods
[0057] 1. Preparation of FeOOH
[0058] Nanorods with different aspect ratios can be synthesized by hydrolyzing FeCl3·6H2O in aqueous solution. FeOOH nanorods with uniform morphology and size were synthesized at a constant temperature of 25°C. The size and morphology of FeOOH nanorods can be further controlled by controlling the reaction time and reaction temperature. The total volume during hydrolysis was 4 L. The concentration of FeCl3·6H2O was 0.04 mol L -1 After a period of reaction, the FeOOH nanorods formed were precipitated to the bottom of the reaction vessel (one month). After removing the supernatant, the FeOOH nanorods were centrifuged and washed three times at 10,000 rpm and then dispersed in 40 mL of water as a stock solution.
[0059] 2. Preparation of R-Fe3O4@PSSMA
[0060] 3mL of FeOOH mother liquor was centrifuged at 8500rpm for 5 minutes, vacuum dried, and the powder was taken to continue the reaction, and 40mL of ethylene glycol was added. Note that the ethylene glycol should be dehydrated with 3A molecular sieves overnight in advance. Then 3.0g of anhydrous sodium acetate, 1.1g of PSSMA, a small amount of ascorbic acid (Vc) and an appropriate amount of water were added, and the beaker was sealed with paraffin film or plastic wrap, and then ultrasonic + magnetic force was used to stir and dissolve alternately. After dissolution, the solution was transferred to a 50mL polytetrafluoroethylene liner and reacted at 190℃ in a muffle furnace for 9 hours. After the reaction was completed, it was cooled to room temperature and washed three times with ultrapure water.
[0061] 3. Preparation of R-Fe3O4@PVP
[0062] 3 mL of FeOOH mother liquor was centrifuged at 8500 rpm for 5 minutes, vacuum dried, and the powder was taken to continue the reaction, and 30 mL of ethylene glycol was added. 0.99 g of sodium acetate, 0.99 g of polyvinyl pyrrolidone, and 0.11 g of glucose were added in sequence, and then the mixed solution was ultrasonically dispersed, and the resulting solution was transferred to a polytetrafluoroethylene liner and reacted at 220°C for 12 hours. After the reaction was completed, it was cooled to room temperature and washed three times with ultrapure water.
[0063] result:
[0064] 1. Selection of iron source:
[0065] The inventors tried to use FeSO4·6H2O, anhydrous FeCl3 and FeCl3·6H2O as the reaction raw materials in order to synthesize uniform β-FeOOH. Figure 1 As shown in the figure, both anhydrous FeCl3 and FeCl3·6H2O can prepare rod-shaped FeOOH. However, the β-FeOOH prepared by anhydrous FeCl3 is not uniformly rod-shaped, but a large part of it is in the shape of a "M", which does not meet our expectations. Therefore, we selected FeCl3·6H2O as our reaction raw material. However, due to the high reaction temperature, the size and morphology of the β-FeOOH prepared by anhydrous FeCl3 are not very uniform. The temperature, reaction time and other conditions will be optimized in the future.
[0066] 2. Optimization of reaction temperature
[0067] The reaction temperature significantly affects the shape and size of iron oxyhydroxide. The hydrothermal method is usually carried out in a closed container. Increasing the temperature will cause positive pressure in the system, which may cause changes in the product shape. Figure 2As shown in the figure, we explored three parallel groups at three different temperatures, namely 87℃, 40℃ and 25℃. In the current experiment, relatively uniform β-FeOOH can be prepared at 25℃ and 40℃, but the particle size of β-FeOOH prepared at 40℃ is still not uniform enough. The morphological particle size of β-FeOOH prepared at 25℃ for one month is uniform. Therefore, in subsequent experiments, we chose to react at 25℃.
[0068] 3. Effects of adding different compounds
[0069] We also investigated the effect of different compounds on the formation of iron oxyhydroxide with uniform particle size. Figure 3 As shown in the figure, adding a small amount of hydrochloric acid during the forced hydrolysis process will cause the generated iron oxyhydroxide to aggregate, while NaH2PO4 has an inhibitory effect on the growth of iron oxyhydroxide. The results show that adding different compounds or surfactants has an effect on the morphology of the final β-FeOOH.
[0070] 3. Impact of reaction time
[0071] Effect of reaction time on the growth of iron oxyhydroxide, such as Figure 4 and Figure 5 As shown in the figure, the iron hydroxide that has grown for one month is 250nm long and 50nm wide. The iron hydroxide that has grown for three months is 450nm long and 100nm wide. After two months of growth, the iron hydroxide has grown nearly twice as large. If the temperature is around 25℃, crystals generally start to grow in a week. If a small particle size is required, the crystal growth time can be shortened.
[0072] In summary, the size of the required oxyhydroxide can be controlled by adjusting the reaction time. At present, most of the reported methods for synthesizing oxyhydroxide are forced hydrolysis methods, which are quick, simple and low-cost, but the morphology and particle size of the synthesized oxyhydroxide nanorods are not uniform, and additional ions need to be added to adjust the morphology and particle size of the nanorods. The room temperature hydrolysis method we adopted can synthesize oxyhydroxide with highly uniform morphology and particle size, and the required particle size of oxyhydroxide can be controlled by controlling the time. In summary, we chose FeCl3·6H2O at a constant temperature of 25°C for 10-100 days to prepare β-FeOOH nanorods.
[0073] 4. Characterization of the performance of iron oxyhydroxide
[0074] Figure 6(a) is the X-ray powder diffraction pattern of the prepared sample. The crystal structure of β-FeOOH was characterized by X-ray diffraction (XRD). CuKa was used as the radiation source, the voltage was 36kV, the current was 20mA, λ=0.154060nm, the maximum power was 3KW, the scanning range was from 10° to 70°, and the scanning speed was 0.02° / s. The XRD test results of the sample were compared with the standard spectrum of β-FeOOH (JCPDS#34-1266). β-FeOOH has obvious diffraction peaks at 11.84°, 16.79°, 26.72°, 34.03°, 35.22°, 39.28° and 55.91°, which are the characteristic diffraction peaks of β-FeOOH. They correspond to the (110), (200), (310), (440), (211), (301), and (521) crystal planes of β-FeOOH, respectively. Figure 6 (b) The wavelength position and intensity of the absorption bands of β-FeOOH were measured by Fourier transform infrared spectroscopy (FT-IR) to analyze its molecular structure. β-FeOOH has absorption bands at 1027, 877, 690 and 3227 cm -1 The characteristic absorption peaks of Fe-O and Fe-O-Fe, -OH appear at
[0075] 5. Polyol reduction method to reduce rod-shaped iron oxyhydroxide to magnetic nanorods
[0076] We used polyol reduction to reduce rod-shaped non-magnetic iron oxyhydroxide to magnetic nanorods and used PSSMA as a protective ligand. PSSMA has abundant anionic groups (-COO - and -SO3 -), PSSMA is modified on magnetic nanoparticles, and the morphology of anisotropic particles can be protected during the phase transformation process. The aqueous dispersion of β-FeOOH nanorods was injected into ethylene glycol solution at 190℃. Ethylene glycol was selected as the reducing agent because the reduction of the polyol solution phase helps to eliminate the close contact of nanoparticles and reduce the possibility of aggregation and agglomeration that is common during high-temperature H2 solid-phase reduction. In addition, compared with H2 reduction, the mild reducing power of polyols can easily control the conversion by fine-tuning the reaction time and temperature. This method is simple and effective, and more importantly, it can be extended to maintain the morphology during chemical transformation of other nanostructures. The key to the concept of surface protection is an effective capping agent, which can stabilize the surface of nanocrystals and prevent them from undergoing obvious morphological changes during chemical transformation. At the same time, the use of polymers as shape-protecting capping agents can greatly reduce the synthesis temperature compared to hydrogen reduction. At the same time, it also solves the problem of poor dispersibility of traditional dense protective layers (SiO2) during high-temperature phase transformation, and greatly improves the synthesis efficiency. In addition, reaction time and reaction temperature are also crucial. The reduction temperature must not be lower than 190°C, otherwise the reduced product will have no magnetism.
[0077] 6. Material Characterization of Magnetic Nanorods
[0078] Figure 7 (b) XRD patterns of the samples of ferric oxyhydroxide and after polyol reduction under surface protection for 4, 8, and 12 h. The phase transition process was further confirmed by X-ray diffraction (XRD) measurements, and the diffraction peaks of the starting materials in the black curve can all be pointed to β-FeOOH (JCPDS#34-1266). Some characteristic peaks of β-FeOOH (i.e., 35°) are very close to Fe3O4, but there is a sharp peak at 27°, corresponding to the (310) reflection of β-FeOOH, which is suitable for monitoring the disappearance of β-FeOOH. From the 4-hour curve, it can be seen that during the reduction process, the peak at 27° gradually disappears with the increase of reaction time, indicating that the transformation of the β-FeOOH phase occurs with the decrease of crystallinity. At the same time, the (220) peak of magnetite appears at 30° and becomes sharper within 8 h, indicating the formation of magnetite with better crystallinity. Based on the absence of the characteristic peak of β-FeOOH at 27° in the 8-hour curve, we conclude that β-FeOOH is completely transformed into magnetite within 8 h. The diffraction pattern of the product after 8 h of reaction has 7 broad peaks at 30.10°, 35.40°, 43.00°, 56.90° and 62.50°, corresponding to (220), (311), (400), (511) and (440) of Fe3O4 (JCPDS#99-0073). Figure 7As shown by the green line in (b), after 12 hours of reaction, characteristic peaks appeared at 24.2, 33.2, and 35.8, corresponding to the (012), (104), and (120) planes of Fe2O3, respectively, and Fe3O4 was transformed into Fe2O3.
[0079] like Figure 7 (d) is shown at 560 cm -1 The peaks at 1052 cm correspond to the Fe-O stretching vibration modes of the tetrahedral and octahedral sites of magnetite. The XRD results are in good agreement with the IR results. The successful binding of PSSMA to the nanorods was confirmed by Fourier transform infrared spectroscopy. -1 Attribution to –SO 3- The symmetric and asymmetric stretching vibrations of 1561 and 1419 cm -1 The peaks are assigned to the symmetric and asymmetric stretching vibrations of –COO-. In addition, the peak of Fe-O at 576 cm -1 ; PVP-coated magnetic nanorods, at 1052cm -1 The peaks observed at 1637 and 1537 cm are attributed to CN stretching, respectively. -1 The energy absorbed by the carbonyl group (C=O) due to its vibration mode. The terminal is due to the stretching of the OH group at 3431 cm -1 A high-intensity broad peak appeared at the surface of magnetite NPs. The presence of different groups such as CN, OH, CH, CC and C=O confirmed the presence of PVP on the surface of magnetite NPs. Fe2p XPS fine scanning spectrum Figure 7 (a) and Figure 7 (c) In the β-FeOOH spectrum, the peaks of fe2p3 / 2 and fe2p1 / 2 are located around 711.5 and 725 eV, respectively, indicating the oxidation state of Fe3+. The peaks of fe2p3 / 2 and fe2p1 / 2 are around 724 eV and 710 eV. The shift of the peaks to lower binding energy can be attributed to the reduction of Fe3+ to Fe2+. Figure 7 As shown in (e), the nitrogen adsorption-desorption isotherm experiment shows that the specific surface area of Fe3O4@PSSMA is 38.246m2 / g.
[0080] 7. Morphological Characterization of Magnetic Nanorods
[0081] By further introducing other capping agents with stronger coordination interactions with iron cations, especially those containing one or more carboxyl groups, such as sodium acetate (NaAc), trisodium citrate (TSC), polyacrylic acid (PAA), and polyacrylic acid sodium salt (PAASS), the morphological deformation of β-FeOOH nanorods during the phase transition can be almost completely suppressed. Figure 8As shown in Figure 2, our research group has tried some new protective ligands, such as PSSMA and PVP, which also showed effective protection capabilities. Fig. 9 As shown in (e), the length of R-Fe3O4@PVP is about 100nm, the width is about 120nm, and the rod-like morphology is relatively well maintained, but the volume shrinks to a certain extent. Fig. 9 As shown in (f), the length of R-Fe3O4@PSSMA is about 350nm, the width is about 50nm, and the rod-like morphology is well maintained.
[0082] 8. Magnetic properties of magnetic nanorods
[0083] like Fig.10 As shown in the figure, the solid powders of Fe3O4@PVP and Fe3O4@PSSMA are both ferromagnetic, and the magnetic fluid solutions formed after the two materials are dissolved in water are also ferromagnetic. Ferromagnetic materials will produce spontaneous magnetic moments under the action of an external magnetic field. These magnetic moments will align in the magnetic field and show obvious magnetism. After the external magnetic field is removed, the ferromagnetic material can retain a certain residual magnetic moment, which is manifested as the residual magnetic moment on the hysteresis loop. Under the action of an external magnetic field, the magnetic moment of the atoms of superparamagnetic materials will be in the same direction as the magnetic field, but the residual magnetic moment will not be retained, that is, its magnetic moment changes rapidly with the change of the magnetic field. After the external magnetic field is removed, the superparamagnetic material will not retain any residual magnetic moment, and the magnetic moment will quickly return to zero. The magnetic fluid we prepared has excellent magnetism and good stability. It can be stored in aqueous solution for a long time, which is conducive to further use in the future. The saturation magnetization intensity value (Ms) can reflect the magnetic response ability of the material. When the external magnetic field is constant, the larger the Ms value, the stronger the magnetic response ability. As Fig.11As shown in the figure, the saturation magnetic susceptibility of the rod-shaped R-Fe3O4@PVP magnetic fluid is greater than that of the spherical Fe3O4@PVP magnetic fluid. Magnetic fluid, also known as magnetic liquid, ferromagnetic fluid or magnetic liquid, is a new type of functional material that has both the fluidity of liquid and the magnetism of solid magnetic materials. It is a stable colloidal liquid composed of magnetic solid particles with a diameter of nanometers (less than 10 nanometers), a base carrier liquid (also called a medium) and a surfactant. The general preparation process of magnetic fluid is to first prepare magnetic nanoparticles, and then evenly disperse the prepared magnetic nanoparticles in the solution; the advantage of magnetic fluid over solid magnetic nanoparticle powder is that after the magnetic nanoparticles are dried in the drying process, they will generally aggregate and agglomerate. The agglomeration of nanoparticles will seriously affect their subsequent properties, and magnetic fluid can effectively improve this shortcoming. The characteristic of magnetic fluid is its stability. The reason for its stability is that the magnetic nanoparticles have been modified and the zeta potential is greater than ±30. Secondly, the particle size of the magnetic nanoparticles used to prepare the magnetic fluid must be small enough to allow the electrostatic repulsion or steric hindrance of the surface-modified magnetic nanoparticles to offset gravity, so that the magnetic fluid can exist stably. The magnetic force on the magnetic nanorods in the aqueous solution is further simulated by COMSOL finite element analysis, such as Fig.12 As shown in the figure, the magnetic nanorods have an easy magnetization axis, which further illustrates the feasibility of using magnetic nanorods as nanostirring bars. In the introduction, we have mentioned that Fe3O4NPs have poor dispersibility and aggregate in water. How to obtain more stable and better dispersed Fe3O4NPs, design new modification methods and develop synergistic materials will be important ways to regulate the activity of Fe3O4NPs and maintain their characteristics. Stable and uniform magnetic fluid provides us with a new idea.
[0084] In summary, the present invention provides a general reaction strategy for preparing magnetic nanorods, which is used to convert non-magnetic templates into highly dispersible anisotropic magnetic nanorods under relatively mild reaction conditions, and the morphology remains intact during the conversion process. The phase transition conditions are relatively mild, which not only helps to improve energy utilization, but also reduces production costs, and also improves the colloidal dispersibility of particles in aqueous solution. The method can also be used for nanospheres and nanocubes. Conceptually, it also updates our understanding of the protective function of protective ligands, not only in the growth of nanostructures, but also in their chemical reactions, which may involve drastic composition and morphological changes. More importantly, the surface protection principle described can be widely used to protect the morphology of nanostructures of various compositions in chemical reactions, thereby greatly promoting chemical transformations and becoming a general and powerful tool for nanostructure synthesis.
[0085] Example 2 Magnetic nanorods as a dynamic nanozyme system for quantitative detection of cysteine
[0086] Abnormal cysteine levels may lead to a variety of diseases, including growth retardation, liver damage, ischemic stroke, etc. Cysteine plays an important role in maintaining skin health and detoxification. Changes in plasma cysteine levels are associated with symptoms such as liver damage, psoriasis, osteoporosis and Alzheimer's disease. Therefore, accurate, rapid and highly selective detection of cysteine content is crucial for life science research and clinical diagnosis.
[0087] Biothiols exist in the human body mainly in the form of low molecular weight thiols or protein thiols, mainly including cysteine (Cys), glutathione (GSH), homocysteine and cysteine residues in proteins; due to the similar structure and sensitivity to the environment of biothiols, the development of new tools to distinguish and dynamically detect them is still a huge challenge. Fig.13 As shown in the figure, we used magnetic nanorods as dynamic nanozymes and used the magnetic responsiveness of magnetic nanorods to enhance their reaction kinetics. 2+ The Fenton-like activity of the nanoparticles is the main reason for their peroxidase activity. The peroxidase substrate can be oxidized by the ·OH produced in the Fenton reaction to generate a colored product. The reducibility of cysteine is used to make the colored product fade, thus constructing a dynamic nanozyme system for quantitative detection of cysteine.
[0088] 1. Self-assembly of R-Fe3O4@PSSMA
[0089] Self-assembled micrometer-scale magnetic chains were observed under a dark-field optical microscope. The orientation and morphology of the magnetic chains can be changed by changing the direction of the magnetic field.
[0090] 2. Characterization of catalytic activity of R-Fe3O4
[0091] The POD-like activity of magnetic nanorods was verified by oxidation of a colorimetric substrate (TMB) in the presence of H2O2. Typically, 10 μL of magnetic nanorods (10 mg / mL) was added to a sodium acetate (NaAc) buffer solution (3 mL, pH 4.0) containing 40 mM H2O2 and 6 mM chromogenic substrate. After incubation at room temperature for 5 minutes, the magnetic nanorods were quickly separated using a magnet (1 minute). The supernatant was collected and its absorption spectrum was determined.
[0092] 4. Actual sample testing
[0093] In order to investigate whether the established UV detection system is suitable for the determination of cysteine in complex matrices, human plasma was used as the actual sample and the plasma sample was diluted 20 times. First, low (6.00μM), medium (11.00μM), and high (18.00μM) concentrations of cysteine were added to the established cysteine detection system using the sample recovery method. Finally, the steps in 3.3.6 were used to detect cysteine and the recovery rate was calculated.
[0094] result:
[0095] 1. Magnetic responsiveness of magnetic nanorods
[0096] Magnetic nanorods have good magnetic properties because of their shape anisotropy, and their shape anisotropy coincides with their easy magnetization axis, and they can rotate with the rotation of the magnetic field, such as Fig.14 As shown. Self-assembled micron-sized magnetic chains were observed under a dark-field optical microscope. It can be seen that the nanoscale magnetic rods self-assembled into micron-sized magnetic chains.
[0097] In order to further explore whether this assembly behavior is due to the mutual attraction of magnetic nanorods or the effect of coated PSSMA, we further observed the self-assembly of PVP-coated magnetic nanorods and magnetic nanospheres. Fig.15 (c) and Fig.15 As shown in (d), no obvious chain aggregates were observed. In addition, we also explored the self-assembly of PSSMA-coated spherical magnetic nanoparticles. Fig.15 (a) and Fig.15 As shown in (b), in the presence of PSSMA, magnetic nanoparticles are more likely to self-assemble into chains. Therefore, we infer that PSSMA is the main factor leading to self-assembly. The direction and morphology of the magnetic chain can be changed by changing the direction of the magnetic field. It can be seen that the magnetic chain rotates with the rotation of the magnetic field. The chain morphology can only be observed in the magnetic fluid state. If the powder morphology is observed, the chain morphology cannot be observed, as shown in Figure Fig.15(e) As shown. Therefore, we can speculate that magnetic fluids have great potential in the direction of colloidal self-assembly and improved aggregation of magnetic nanoparticles. Compared with single nanoparticles or random aggregates, the ordered arrangement of nanoparticles usually leads to extraordinary collective properties, which can cleverly exploit the synergistic effects between adjacent building blocks to significantly enhance the optical, plasmonic, catalytic, magnetic and mechanical properties. However, obtaining such an ordered arrangement is a difficult task. One of the most promising strategies is colloidal self-assembly, the spontaneous organization of colloidal nanoparticles due to direct specific interactions that are usually related to thermodynamic equilibrium. Various self-assembly methods have been reported to have achieved great success in spherical nanoparticles. However, when non-spherical nanoparticles are used as building blocks, most self-assembly methods lead to unsatisfactory long-range stacking due to the lack of effective orientation control of the nanoparticles. PSSMA has abundant anionic groups (-COO - and -SO3 - ), PSSMA is modified on magnetic nanoparticles, the morphology of anisotropic particles can be protected during the phase transition process, and magnetic nanorods or magnetic nanoparticles can self-assemble into magnetic chains with magnetic responsiveness. The polymer used in this experiment provides a new idea for the self-assembly of magnetic nanoparticles.
[0098] The magnetic chain modified with PSSMA is negatively charged, and its stability increases with the increase of pH, as shown in the figure Fig.15 As shown in (f), Zeta potential is an important parameter used to measure the strength of mutual repulsion or attraction between particles. Generally speaking, the smaller the molecule or dispersed particle, the higher the absolute value of its Zeta potential, which means that the system is more stable and can better resist aggregation. On the contrary, when the Zeta potential is lower, the system is more likely to condense or agglomerate, which means that the attraction exceeds the repulsion. Therefore, the absolute value of the Zeta potential directly represents the stability of the particle, while its positive or negative value indicates the charge of the particle.
[0099] In addition, as the dynamic magnetic field stirring speed increases, the relative activity of the reaction also increases, e.g. Fig.16 As shown, the relative activity of the reaction can be increased to three times when no dynamic magnetic field is applied. This further illustrates that the nanochains self-assembled from magnetic nanorods are responsive to magnetic fields and have the potential to act as stirrers in small volume reactions.
[0100] 2. Verification of the catalytic activity of magnetic nanorods
[0101] like Fig.17 As shown, containing Fe 2+The magnetic nanorods can be used as a nanozyme to exhibit peroxidase-like activity. They can catalyze H2O2 to produce hydroxyl radicals (·OH) and oxidize the artificial substrate TMB to produce the blue oxidized product oxTMB. Other substrates of peroxidase include o-phenylenediamine (OPD) and 2,2-azino-bis(3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt (ABTS). Fig.17 As shown in (a), when OPD is used as a substrate, the increase of the characteristic peak at 450nm can be observed in the full wavelength scanning experimental results after the addition of Fe3O4 nanorods, and the solution changes from colorless to yellow before and after the reaction. When ABTS is used as a substrate, the appearance of a characteristic peak at 417nm is observed in the full wavelength spectrum of the reaction solution containing magnetic nanorods, and the reaction solution changes from colorless to blue-green. The oxidation characteristics of these substrates are similar to the catalytic behavior of natural peroxidase. The activity of magnetic nanorods was characterized by using TMB as a substrate, and the peroxidase-like activity of the R-Fe3O4@PSSMA nanocomposite material was tested in the H2O2-TMB system using a UV-visible spectrometer. As shown Fig.17 (b) shows that when H2O2-TMB exists alone, there is no absorption peak. When H2O2-TMB and R-Fe3O4@PSSMA coexist, the absorption peak is significantly higher than that of H2O2-TMB alone. When the prepared R-Fe3O4@PSSMA composite material is added, there is an extremely obvious absorption peak at 652nm, and the color of the reaction solution also changes from colorless to blue. The appearance of characteristic peaks and typical color changes can prove that the magnetic nanorods have peroxidase-like activity. This shows that R-Fe3O4@PSSMA can effectively catalyze H2O2, proving that it has good catalytic activity. In addition, under the action of a magnetic field, the absorbance is significantly enhanced, proving that the concept of dynamic nanozymes is established.
[0102] In order to explore the reactive oxygen species (ROS) in the reaction process of R-Fe3O4@PSSMA, such as hydroxyl radical (·OH), superoxide radical (·O2 - ) were generated, sodium azide, DMSO, methanol, etc. were used to capture the above free radicals. The results showed that when DMSO was added to the R-Fe3O4@PSSMA / TMB / HO system, the absorbance of the system was greatly reduced, such as Fig.17 (d) indicates that ·OH is produced during the reaction of the system, and ·OH is dominant. In addition, the ·OH signal produced in the reaction system was further detected by electron spin resonance (ESR). Fig.17As shown in (c), an obvious ·OH signal peak was detected under the conditions of R-Fe3O4@PSSMA / H2O2, and the ESR signal of ·OH also increased with the increase of illumination time. This further proves that ·OH was produced under the catalysis of R-Fe3O4@PSSMA nanozyme. In general, these results indicate the possible mechanism of magnetic nanorods as peroxidases: first, H2O2 is absorbed by the surface of magnetic nanorods and activated by the iron ions in the magnetic nanorods, then the OO bond in H2O2 is split to generate ·OH and stabilized on the MNE surface. Finally, TMB is strongly oxidized to ·OH to generate a blue product.
[0103] 3. Actual sample testing
[0104] In order to investigate whether the established UV detection system is suitable for the determination of cysteine in complex matrices, human plasma was used as the actual sample, and the plasma sample was diluted 20 times. First, low (6.00μM), medium (11.00μM), and high (18.00μM) concentrations of cysteine were added to the established cysteine detection system using the sample recovery method. The results are shown in Table 1 below. The recovery rate in plasma samples is in the range of 91.81-129.4%, and RSD is <3.5%, indicating that the system has good accuracy and repeatability in the determination of cysteine in plasma samples and has good applicability in complex samples.
[0105] Table 1 Serum sample recovery rate determination results
[0106]
[0107] The magnetic nanorods prepared by the present invention can self-assemble into magnetic chains with magnetic responsiveness and micrometer level through modified polymer ligands (PSSMA). In addition to magnetic field responsiveness, the magnetic chain also has peroxidase-like activity, and we use it as a dynamic nanozyme. It can effectively improve the reaction kinetics of the nanozyme, and the relative activity of the reaction can be increased to 3 times when no dynamic magnetic field is added. The material has reasonable potential applications as a nanosensor in similar systems. Therefore, we hope to use magnetic nanorods in microfluidic systems to achieve quantitative detection of analytes.
Claims
1. A method for preparing magnetic nanorods, characterized in that: Follow these steps to achieve this: (1) Preparation of β-FeOOH nanorods β-FeOOH nanorods were synthesized by hydrolyzing FeCl3·6H2O in aqueous solution; the concentration of FeCl3·6H2O was 0.01-0.04 mol L at a constant temperature of 25°C. -1 After 10-100 days of reaction, the formed β-FeOOH nanorods are precipitated to the bottom of the reaction container to form a β-FeOOH nanorod solution; (2) Preparation of R-Fe3O4@PSSMA 3 mL of β-FeOOH nanorod solution was centrifuged at 8500 rpm for 5 minutes, vacuum dried, 20-80 mL of ethylene glycol was added, and then 0.3-10 g of anhydrous sodium acetate, 0.5-2.0 g of (poly (4-styrenesulfonic acid-co-maleic acid) sodium PSSMA), 5-50 mg of ascorbic acid and water were added, and stirred to dissolve; the solution was reacted in a muffle furnace at 190-250° C. for 6-12 hours to obtain magnetic nanorods R-Fe3O4@PSSMA; (3) Preparation of R-Fe3O4@PVP 3 mL of β-FeOOH nanorod solution was centrifuged at 8500 rpm for 5 minutes, vacuum dried, and the powder was taken to continue the reaction, and 30 mL of ethylene glycol was added. 0.3-10 g of sodium acetate, 0.5-2.0 g of polyvinyl pyrrolidone, and 0.11 g of glucose were added in sequence, and then the mixed solution was ultrasonically dispersed, and the resulting solution was transferred to a polytetrafluoroethylene liner and reacted at 220 ° C for 12 hours to obtain R-Fe3O4@PVP.
2. The magnetic nanorods prepared according to the method of claim 1 are used as peroxidase.